Conservatism and innovation in the Hebrew language of the Hellenistic period : proceedings of a fourth International Symposium on the Hebrew of the Dead Sea Scrolls and Ben Sira - Joosten, Jan.; Rey, Jean-Sébastien. (Studies on the Texts of the Desert of Judah, 2008)
This volume contains 15 contributions presented at a symposium on the Hebrew of the Dead Sea Scrolls andamp; Ben Sira, held in Strasbourg on May 29 and 30, 2006. The papers address linguistic and philological issues. They seek to relate the Hebrew texts of the Hellenistic period to earlier and later traditions. Among the authors are some of the most eminent Hebraists of our period as well as some younger scholars. The papers throw new light on the interpretation of the Qumran Scrolls, of the Apocrypha and of the Hebrew Bible.